Development and characterization of a novel liquid crystalline system containing sodium alginate for incorporation of trans-resveratrol intended for treatment of buccal candidiasis - Miyashiro, C. A. [UNESP]; Bernegossi, J. [UNESP]; Bonifácio, B. V. [UNESP]; de Toledo, L. G. [UNESP]; Ramos, M. A.S. [UNESP]; Bauab, T. M. [UNESP]; Chorilli, M. [UNESP] (My University, 2020)
Trans-resveratrol has antimicrobial effects; however, its hydrophobic properties hamper its incorporation into pharmaceutical formulations. The aim of this study was to develop liquid crystals and a liquid crystal precursor (microemulsion), a common nanotechnology-based drug delivery system using a surfactant, an oil phase, and a polymer dispersion, for topical administration against buccal candidiasis. A ternary diagram was constructed and a potential formulation was selected, in order to run characterization tests. We chose the formulation that presented microemulsion and crystal liquid characteristics through polarized light microscopy and small-angle X-ray scattering experiments. The stability and structural features of the formulations were observed by performing rheological assay, measuring mucoadhesion, and analyzing texture profiles. It was verified that the chosen system was capable of transiting from microemulsion to liquid crystals when added in aqueous phase; further, the presence of sodium alginate as the polymer increased its mucoadhesion strength. Microbiological assay of trans-resveratrol, using amphotericin B and fluconazole as controls against strains of Candida albicans, showed positive anti-microbiological effect; however, a high concentration of the compound was needed.